2005
DOI: 10.1186/1476-4598-4-3
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Pituitary tumor transforming gene1 (PTTG1) is a novel oncogene that is expressed in most tumors. It encodes a protein that is primarily involved in the regulation of sister chromatid separation during cell division. The oncogenic potential of PTTG1 has been well characterized in the mouse, particularly mouse fibroblast (NIH3T3) cells, in which it induces cell proliferation, promotes tumor formation and angiogenesis. Human tumorigenesis is a complex and a multistep process often requiring concordant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…Some of the most highly connected genes within the MCM already have been identified as potential cancer targets (topoisomerase II␣, ARKB, PTTG1͞sercuin, Survivin, and EZH2) (23)(24)(25)(26)(27). To identify a potential novel gene target, we looked for the most highly connected genes that have not been extensively studied as cancer targets.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the most highly connected genes within the MCM already have been identified as potential cancer targets (topoisomerase II␣, ARKB, PTTG1͞sercuin, Survivin, and EZH2) (23)(24)(25)(26)(27). To identify a potential novel gene target, we looked for the most highly connected genes that have not been extensively studied as cancer targets.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of human PTTG in mouse NIH3T3 fibroblasts and human embryonic kidney (HEK293) cells resulted in increased cell proliferation, induction of cells to form foci in monolayer culture and promotion of tumor formation in nude mice (24,26,27,72). These results clearly suggest that PTTG is a human oncogene.…”
Section: Tumorigenesismentioning
confidence: 86%
“…(176,177). In previous studies, we (72) showed that PTTG stimulates the expression of bFGF, VEGF and IL-8, which may Baltimore. Maryland) (89).…”
Section: Invasion Index Of Huvecmentioning
confidence: 88%
See 2 more Smart Citations